SIGNIFICANCE OF PSYCHOLINGUISTIC RESEARCH (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article talks about the conditions for the emergence of psycholinguistics. That is, the direction of linguistic psychology, its uniqueness and necessity today. His role in the process of perception and understanding of text has not yet been sufficiently studied, which, in turn, requires serious attention to the issue of determining the rules for text analysis and semantic perception.